THE COMPOSITION OF LONG LINE CATCHES IN THE MORNING AND DAY DAY IN THEWATERS OF NARAS 1 OF PARIAMAN SUBDISTRICT IN NORTH WEST SUMATRA PROVINCE - Yurnida Yurnida; Pareng Rengi; Arthur Brown (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted on July 2017 in the waters of Naras Village 1 of Pariaman Subdistrict in North Sumatra. The method used in the study is a survey and research method conducted for 10 consecutive days. This study aims to determine the number of differences and the composition of the catch in the morning and afternoon. the results of this study were obtained to be used as information material for those who need it.The results of the study regarding the composition of longline catches in the morning were 331.8 kg (189 tails) while in the afternoon 144.7 kg (84 tails). the catch obtained by longline catches during the study consisted of 5 species namely snapper (Epinephelus SP), layur fish (trichiurus lepturus), malang fish (muraenesa SP) seen from daily catches in the morning more catches compared to daytime.Keyword :demesal fish, long line, Pariaman waters